Association of Intraoperative Antibiotic Irrigation With Systemic Contact Dermatitis - Jodi So; Nathalie Mie Suzuki; Jennifer K. Chen; Silvina Pugliese; Bernice Y. Kwong; Lina Meng; Golara Honari (2022)
This case series describes the development of morbilliform drug eruption after breast surgery.